Is transcanal tympanoplasty an appropriate surgical treatment for congenital middle ear cholesteatoma with ossicular involvement?. (January 2019) - Kim, Hantai; Yoo, Shin Young; Choung, Yun-Hoon; Park, Hun Yi
Abstract: Objectives: The aims of this study are to analyze the clinical characteristics of congenital middle ear cholesteatoma (CMC), to evaluate the treatment results according to the types of surgical approach, and to suggest the appropriate surgical treatment option in each stage. Methods: One hundred fifteen children (≤15 years old) with surgically confirmed CMC, who underwent surgery at a tertiary hospital during 1994–2012 and were followed up more than 2 years, were enrolled in this study. CMC was classified into four stages by the staging system proposed by Potsic. Clinical characteristics of CMC were analyzed and its association with the rate of residual disease was evaluated. Results: Based on the location of the lesion, posterior-origin CMCs were detected significantly later (5.5 years old, P  = 0.018) and more likely to be in the Stage 3 or 4 ( P  < 0.001). Residual CMCs were observed in 10 out of 115 cases (8.7%) and were more frequent in the Stage 3 or 4 patients ( P  = 0.007). However, the rate of the residual disease was not statistically different between anterior- and posterior-origin CMCs ( P  = 0.101). All 58 cases of CMC in the Stage 1 or 2 were successfully removed by transcanal tympanoplasty with only one residual case (1.7%). In the Stage 3 cases, transcanal tympanoplasty was conducted in 24 out of 29 patients, and the residual disease rate was 12.5% (3 out of 24). Conclusions: The early stages of CMC were likely to be diagnosed at younger age, and the early diagnosis seemed to show better surgical outcomes with less invasive techniques. Transcanal tympanoplasty can be an effective surgical option for CMCs in the Stage 3.